EXPLORING ENTREPRENEURIAL INTENTION THROUGH INTEREST, SKILLS, AND STARTER KIT ASSISTANCE AMONG EMPOWERNCER PARTICIPANTS - Vasudavan, Ganesan; Salleh, Mad Ithnin (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This study investigates the determinants of entrepreneurial intentions among participants of the empowerNCER programme in Batang Padang, Malaysia. The research focuses on three critical factors which are entrepreneurial interest, skills, and starter kit assistance, which are considered essential for fostering entrepreneurship in socio-economic empowerment initiatives. A quantitative research design was adopted, utilizing a structured questionnaire distributed to 438 respondents enrolled in the empowerNCER programme. Data were analysed using SPSS, applying descriptive statistics and multiple regression analysis to assess the predictive strength of the selected variables. The findings reveal that entrepreneurial skills emerge as the most dominant factor influencing entrepreneurial intentions, followed by starter kit assistance and interest. Regression analysis confirms that skills have the strongest predictive effect, indicating that capability development plays a more significant role than material support or motivational aspects. These results suggest that while providing starter kits and stimulating interest are beneficial, skill enhancement remains the cornerstone for entrepreneurial success. The study underscores the importance of integrating skill development programmes with material assistance and motivational strategies to strengthen entrepreneurship initiatives. Policymakers and programme designers should prioritize comprehensive training modules alongside resource provision to ensure sustainable entrepreneurial growth. This research contributes to the understanding of entrepreneurship development within empowerment programmes and offers actionable insights for improving policy frameworks and implementation strategies.